Pharmacokinetics-Pharmacodynamics of a Sordarin Derivative (GM 237354) in a Murine Model of Lethal Candidiasis - Aviles, P. (American Society for Microbiology, 2000)
Sordarins are a new class of antifungal agents which selectively inhibit fungal protein synthesis (FPS) by impairing the function of elongation factor 2. The present study investigates possible correlations between sordarin pharmacokinetic (PK) properties and therapeutic efficacy, based on a murine model of invasive systemic candidiasis, and provides a rationale for dose selection in the first study of efficacy in humans. A significant correlation between PK parameters and the in vivo activity of GM 237354, taken as a representative FPS inhibitor, was demonstrated in a murine model of lethal systemic candidiasis. Area under the concentration-time curve (AUC) and maximum concentration of drug in serum (C(max)) over 24 h were determined after a single GM 237354 subcutaneous (s.c.) dose (50 mg/kg of body weight) in healthy animals (no significant PK changes with infection were observed for other sordarin derivatives). These results have been used to simulate PK profiles obtained after several doses and/or schedules in animal therapy. A PK-pharmacodynamic (PD) parameter such as the time that serum drug concentrations remain above the MIC (t > MIC) was also determined. Treatment efficacies were evaluated in terms of the area under the survival time curve (AUSTC), using Kaplan-Meier survival analysis and in terms of kidney fungal burden (log CFU/gram) after s.c. doses of 2.5, 5, 10, 20, and 40 mg/kg every 4, 8, or 12 h (corresponding to total daily doses of 5 to 240 mg/kg). The results show all treatments to significantly prolong survival versus that of infected and nontreated controls (P < 0.05). Relationships between simulated PK and PK-PD parameters and efficacy were explored. A good correlation independent of the dosing interval was observed with AUC (but not C(max) or t > MIC) and both AUSTC and kidney burden. Following repeated dosing every 8 h, AUC(50) (AUC at which 50% of the maximum therapeutic efficacy is obtained) was estimated as 21.7 and 37.1 μg · h/ml (total concentrations) for AUSTC and kidney burden using a sigmoid E(max) and an inhibitory sigmoid E(max) PK-PD model, respectively. For an efficacy target of 90% survival, AUC was predicted as 67 μg · h/ml. We conclude that the PK-PD approach is useful for evaluating relationships between PK parameters and efficacy in antifungal research. Moreover, the results obtained with this approach could be successfully applied to clinical studies.